Global migration: Implications for international business scholarship - Hajro, Aida; Brewster, Chris; Haak-Saheem, Washika; Morley, Michael J. (Journal of International Business Studies, 2023)
Migration is increasingly viewed as a high-priority policy issue among politicians, intergovernmental organizations, NGOs, and civil society throughout the world. Its implications for the private sector, for economic prosperity, and for the cross-border activities of firms are undeniable and likely to grow in importance. Yet, despite its relevance to International Business, treatment of migration in the mainstream International Business literature has been limited. In this contribution, we set out key aspects of migration that are germane to International Business. Specifically, we suggest recent migratory shifts are transforming important elements of the context in which multinational enterprises operate, with significant implications for their international human resource management practices, for firms' entry modes and market selection approaches, and for the manner in which international strategies are formulated and implemented. We offer a research agenda to motivate International Business scholars to study global migration in more depth and to reevaluate the generalizability of aspects of their theories in light of developments in global migration.